Boganmeldelser - Järvinen, Margaretha; Espersen, Ole; Simonsen, Jørn; Greve, Vagn; Nielsen, Beth Grothe; Hauge, Ragnar; Garde, Peter; Pihlajamäki, Heikki (Nordisk Tidsskrift for Kriminalvidenskab, 1991)
Book reviews